Efektivitas Latihan Berbasis Sensor IMU dengan Umpan Balik Real-Time terhadap Peningkatan Akurasi, Kecepatan, dan Konsistensi Shooting Sepak Bola pada Mahasiswa PJOK - Yogi Ferdy Irawan (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Shooting ability is a fundamental skill in soccer that determines goal-scoring productivity. However, conventional training methods still rely on subjective feedback from coaches without measurable objective data. This study aims to analyze the effectiveness of Inertial Measurement Unit (IMU) sensor-based training with real-time feedback on improving accuracy, velocity, and consistency of soccer shooting among Physical Education, Sport and Health (PJOK) students. The research method used a pretest-posttest control group experimental design involving 48 PJOK students randomly divided into experimental group (n=24) and control group (n=24). The experimental group performed shooting training with IMU sensors attached to their feet providing visual feedback through a smartphone application, while the control group performed conventional shooting training without technology. The training program was conducted for 8 weeks with a frequency of 3 times per week. Measurement instruments included the Loughborough Soccer Shooting Test for accuracy, Stalker ATS II radar gun for ball velocity, observation rubric for biomechanical technique, and coefficient of variation for consistency. Data analysis used Analysis of Covariance (ANCOVA) with significance level α=0.05. The results showed that the experimental group experienced significant improvements in shooting accuracy (19.7% vs 8.3%, p<0.001, η²=0.412), ball velocity (11.2% vs 4.8%, p<0.001, η²=0.385), biomechanical technique quality (23.1% vs 9.4%, p<0.001, η²=0.441), and performance consistency with CV reduction from 14.2% to 8.7% (p<0.001). The conclusion of this study is that IMU sensor-based training with real-time feedback is proven effective in improving all aspects of soccer shooting ability among PJOK students with large effect size category, thus can be recommended as an innovative training method in sports education